EFFECTS OF NACI STRESS ON THE GENOME STRUCTURE STABILISATION OF RICE ORYZA SATIVA CELLS LONG-TERM CULTURED IN VITRO - Thuỷ, Nguyễn Thanh; Bình, Đỗ Quang (Vietnam Journal of Biotechnology, 2011)
In vitro culture of plant cells is a useful tool for studies relating the biological fransformation from a single cell  to  the  whole  plant  in vitro. Using  the  in vitro technology,  researchers  are  able  to  not  only  confrol  the biological reaction chains but also to create a number of new products other than those ofthe  initial materials. However,  growing  in  the  in  vitro  artificial  conditions  for  a  long  time,  plant  cells  could  not  avoid  the phenomenon  of  soma  variation.  The  level  of  variation  of  the  cultured  cells  depends  on  various  factors, including the genotype and physiological state of initial materials, the culture conditions, the culture time, etc. This study presents results relating the molecular changes in the genome of rice (Oryza sativa) cells that have been cultured for a long time in different  salt (NaCI) sfress conditions by RAPD technique. In comparison with the  initial  material,  not  derived  from  the  culture  in  vitro  of  isolated  cells,  genome  of  cells  cultured  in  a condition without NaCI sfress bears more molecular changes than that of cells continuously cultured in the salt sfress  condition.  Though  cells  of the two culture  conditions  shared  several  specific  changes, induced  by the long-term culture in vitro, the salt sfress adapted cells shared more common similarities with the initial material than  the  non  sfressed  cells.  Results  obtained  from  the  present  study  are  in  accordance  with  our  previous observations, carried out at the cell level, that the totipotency ofthe  isolated rice cells has been stabilized much better in the suitable salt sfress culture condition than in the condition without the sfress  factor